Monetary policy shocks and the dynamics of agricultural commodity prices: evidence from structural and factor‐augmented VAR analyses. (8th November 2016) - Alam, Md Rafayet; Gilbert, Scott
Abstract: Fluctuation in commodity prices is a significant and timely issue to be studied. This study is to examine the impact of monetary policy and other macroeconomic shocks on the dynamics of agricultural commodity prices. The major contributions of this study are twofold. First, unlike other studies that use indexes, this study analyzes the commodities individually, affording the inclusion of commodity‐specific fundamentals such as the level of inventory—an important determinant of commodity price—in a structural VAR framework. Second, it exploits a rich data set of agricultural commodity prices which includes commodities that are usually overlooked in the literature, and extracts a common factor using the dynamic factor model to understand the extent of comovement of the prices and to gauge the extent to which macroeconomic shocks drive the "comovement" in a factor‐augmented VAR (FAVAR) framework. The findings show that monetary policy, global economic conditions, and the U.S. dollar exchange rates play an important role in the dynamics of agricultural commodity prices.